Pengembangan Four-Tier Diagnostic Test Berbasis Website untuk Mengidentifikasi Miskonsepsi pada Materi Suhu dan Kalor - Lolika Saputri; Maison Maison; Wawan Kurniawan (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
The aim of this study was to develop a web-based four-tier diagnostic test to identify junior high school stduent’s misconceptions in temperature and heat. This research is a type of development research (Research and Development) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). However, in research it is only limited to the Development stage because the research objectives have been achieved. The data collection instrument was in the form of a media expert validation questionnaire. The research data includes quantitative data in the form of validator evaluation and qualitative data in the form of comments and suggestions given by the validator. The results showed that the product was suitable for use based on expert validation with the very feasible category. The resulting product has two main parts, namely the four-tier diagnostic test and data from the analysis of the four-tier diagnostic test.